A code offloading scheme for big‐data processing in android applications. (9th May 2014) - Hung, Shih‐Hao; Tzeng, Tien‐Tzong; Wu, Gyun‐De; Shieh, Jeng‐Peng; You, Ilsun; Ogiela, Marek R.; Hwang, Myunggwon
Summary Smart mobile devices and wireless networks are changing the way people execute applications and access information. In the meantime, more and more personal data are thus spread around different data silos in the Internet. One day, you will find that you may want to access your own data, but the service providers may not allow or the vendors do not provide any application for your need. It means your personal data are locked in by the service vendors. While the advances in the hardware/software technology of the smart mobile devices enable more complicated application than the user can image a couple of years ago, those devices still fall short of big storage, powerful computing and more battery capacity for better user experience. The user may expect a device with secure and unlimited storage for his personal data and run his application as he wishes without incurring more energy consumption. So far, no simple solutions have been proposed to enable compute cloud for code offloading Android application and trusted storage cloud for personal data. The work described in this paper enhances current Android application framework to address the aforementioned issues. We introduce the MobileFBP framework to augment the compute part for the Android device and propose to leverage the central storage part with personal data store, that is, PDS, for trusted usage. In addition to the design and implementation of the enhanced framework, our preliminary experimental results are illustrated as well. Copyright © 2014 John Wiley & Sons, Ltd.